Aesthetic management with bleaching external without light activation: Penatalaksanaan estetik dengan bleaching eksternal tanpa penyinaran - Risnawati; Christine Anastasia Rovani (Makassar Dental Journal PDGI Makassar, 2023)
The occurrence of tooth discoloration on one or more anterior teeth can significantly interfere with the aesthetics of the smile, thus encouraging patients to seek aesthetic dental treatment. One of the most popular dental aesthetic procedures is external bleach-ing treatment. This case report describes about management of teeth discoloration with external bleaching using bleaching agent 40% hydrogen peroxide (H2O2) without light activation. A 27-year-old female came to the Dental Hospital of Universitas Ha-sanuddin with complaints of yellowish upper and lower teeth. The patient feels less confident and wants the teeth look white and brighter. The external bleaching procedure is preceded by initial color determination score of 7 with an opalescence boost shade guide. A dental optragate was placed in the patient’s mouth, followed by cleaning the surface of the teeth with a brush and pumice, application of an astringent, gingival barrier in the upper and lower teeth. Application of 40% H2O2 bleach agent for 20 minutes, then cleaned, desensitizing agent application, and final color adjustment with score of 4. It is concluded that external bleaching with 40% H2O2 without light activation effectively whiten teeth and reduce the risk dentin hypersensitivity.